Coming to your senses : there's more to product experience than meets the eye. - Meenakshi Shunmugham. (2009)
Our senses are the first gateway to our perception of the world. Information gleaned from the various senses is integrated to generate a holistic human experience. A great deal of research has found vision to dominate and guide the human experience more so than any other senses. However, the emergence of touch as an important sense in consumer behaviour seems to indicate that vision’s importance in certain domains of human experience might have been previously overestimated.